Study on strength and ductility of concrete filled steel tubular short columns under concentric loading - Gupta, P. K.; Prasad, J.; Singh, Y. C. (Journal of Structural Engineering, 2024)
In this paper experimental studies on short, concentrically loaded concrete filled steel tubular columns are presented. Columns having diameters between 140 and 200 mm and lengths between 300 and 500 mm were tested under axial compression. The concrete mix design was done as per Indian Standard IS:10262-198416. The columns were divided into three categories viz. bare, concrete filled tubes and concrete filled tubes with longitudinal and transverse reinforcement to investigate their load carrying capacity and ductility. Measured column strengths are compared with the values predicted by Eurocode 4¹³, AISC(2005)¹⁴ and Canadian codes (2002)¹⁵. The categorization has been done to compare their mode of failure, yield and post yield behavior. The effect of these parameters on the confi nement of the concrete core was studied. Based on the obtained results it can be summarized that the provision of external reinforcement in Concrete filled tubes (CFTs) decides the mode of deformation and improves the load carrying capacity of CFTs in general. All three codes predicted lower values than that measured during the experiments. Euro code 4 gives the best estimation for both types of CFTs (concrete filled tubes and concrete filled tubes with longitudinal and transverse reinforcement).